Variasi Lebar Pelat Terhadap Daya Dukung Aksial Tarik Fondasi Tiang Helikal Di Tanah Gambut - Tiara Mahardika; Ferry Fatnanta; Syawal Satibi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Helical piles is one of the alternative to replace wood pile at a construction over peat soil. Determination of uplift capacity from field test in this research will be interpreted by intersection of tangent method. Uplift capacity of helical pile theoritically calculated using two approches design with individual plate bearing method and cylindrical shear method. This study compared helical pile used diameter 35 cm, 25 cm and 15 cm with variations, wood pile, and pile without helix. The result of the study confirmed that uplift capacity will be increasing with the increment of helix plate diameter and the number of helix. Based on the interpretation data from field test, the capacity of helical pile is closer calculation cylindrical shear method than individual plate bearing method which means uplift capacity of helical pile is derived from shear resistance along cylindrical failure surface and bearing resistance above the top or bottom helix. And other result confirmed that helical pile has the greater uplift capacity than wood pile or pile without helix.Keywords: Helical pile, wood pile, pile without helix, peat soil, helix plate diameter, uplift capacity